2011
DOI: 10.2147/opth.s21453
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal bevacizumab with or without mitomycin C trabeculectomy in the treatment of neovascular glaucoma

Abstract: Purpose:To demonstrate the role of intravitreal bevacizumab in regression of iris neovascularization, and intraocular pressure (IOP) control in neovascular glaucoma.Methods:A retrospective random case series study was performed. Twenty eyes of 20 patients who presented with neovascular glaucoma were treated with intravitreal bevacizumab 2.5 mg in 0.1 mL. Retinal photocoagulation was performed for all cases as soon as possible after intravitreal injection and subscleral trabeculectomy with mitomycin C 0.4 mg/mL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Another study performed by Ozsutcu et al evaluated the use of an intraoperative bevacizumab injection, with the same dosage, associated with pterygium excision with rotational conjunctival flap followed by another injection after 1 week, reporting significantly less recurrence than rotational flap alone [30]. No side effects related to bevacizumab injection were observed in any previous study [3133]. …”
Section: Discussionmentioning
confidence: 99%
“…Another study performed by Ozsutcu et al evaluated the use of an intraoperative bevacizumab injection, with the same dosage, associated with pterygium excision with rotational conjunctival flap followed by another injection after 1 week, reporting significantly less recurrence than rotational flap alone [30]. No side effects related to bevacizumab injection were observed in any previous study [3133]. …”
Section: Discussionmentioning
confidence: 99%
“…However, SO tamponade may lead to the elevation of IOP, which probably result in irreversible loss of vision. Marey et al [ 29 ] reported the effect of preoperative IVB injection before trabeculectomy for NVG. The results showed that the mean preoperative IOP dropped from 41.45 ± 5.89 mmHg to 19.3 ± 5.5 mmHg and 17.75 ± 3.74 mmHg at 6 months and 12 months postoperatively, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Several other studies examining the effect of anti-VEGF on NVG patients found no statistically significant change between trabeculectomy with anti-VEGF to trabeculectomy with MMC or 5-FU. 16,2632 The success rates of those studies were lower (between 50% and 80% for all groups); however, for cases of NVG, an additional benefit favoring intracameral anti-VEGF was rapid regression of iris neovascularization. 2628…”
Section: Discussionmentioning
confidence: 97%